Antimicrobial resistance of Staphylococcus spp. isolated from canine specimens submitted to a veterinary diagnostic laboratory in South Africa - Themba Titus Sigudu; James W. Oguttu; Daniel N. Qekwana (Veterinary World)
Background and Aim: The rising burden of antimicrobial resistance (AMR) in veterinary medicine poses significant threats to animal and public health. In South Africa, inadequate surveillance exacerbates the challenge, particularly regarding Staphylococcus spp. infections in companion animals. This study aimed to investigate the patterns and predictors of AMR and multidrug resistance (MDR) in Staphylococcus isolated from dogs between 2012 and 2017.